Analisis Pengembangan Komponen Kurikulum Pendidikan Islam di Madrasah Diniyah - Salman Alfarisi (Rayah Al-Islam, 2020)
A mosque is a place of worship for Muslims whose function is not only for worship but also as a place to learn religious knowledge. And it lasted from the time of the Prophet to the Caliphate of the Saljuk Bani. At that time science developed rapidly, there were many book translation activities, halaqoh activities or recitation activities of the masyaikhs and students increased in number. Students or students who take part in learning in the mosque, because the mosque as a learning center can no longer accommodate student learning activities, a madrasah is established as a special place to study Islam. Realizing the importance of the existence of madrasah diniyah in the boarding school environment, the researcher wants to reveal the madrasah curriculum model and curriculum development, so that graduates have competencies in accordance with the expectations of all parties. This type of research uses qualitative research, descriptive, library research, which aims to describe a situation or phenomenon as it is by taking data sources from various documents that support this research with documentation study.